Urine Tenofovir Levels Measured Using a Novel Immunoassay Predict Human Immunodeficiency Virus Protection. (22nd June 2020) - Stalter, Randy M; Baeten, Jared M; Donnell, Deborah; Spinelli, Matthew A; Glidden, David V; Rodrigues, Warren C; Wang, Guohong; Vincent, Michael; Mugo, Nelly; Mujugira, Andrew; Marzinke, Mark; Hendrix, Craig; et al.
Abstract: New tools are needed to support pre-exposure prophylaxis (PrEP) adherence for human immunodeficiency virus (HIV) prevention, including those that enable real-time feedback. In a large, completed PrEP trial, adequate urine tenofovir levels measured using a novel immunoassay predicted HIV protection and showed good sensitivity and specificity for detectable plasma tenofovir.